2022
DOI: 10.1136/jitc-2021-004006
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen facilitates teniposide-induced cGAS-STING activation to enhance the antitumor efficacy of PD-1 antibody in HCC

Abstract: BackgroundEmerging evidence indicates that the cyclic GMP-AMP synthase-stimulator of interferon genes (cGAS-STING) axis plays a pivotal role in intrinsic antitumor immunity. Previous studies demonstrate that the conventional chemotherapy agent, teniposide, effectively promotes the therapeutic efficacy of programmed cell death protein-1 antibody (PD-1 Ab) through robust cGAS-STING activation. Unfortunately, the cGAS expression of tumor cells is reported to be severely suppressed by the hypoxic status in solid t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Studies have shown that atmospheric and hyperbaric hyperoxia can reduce the hypoxic area of tumors to varying degrees. [300][301][302][303] The EPO levels in hepatoblastoma HepG2 cells treated with 5% O 2 and 1% O 2 were 2.5 and 4 times higher than those in cells treated with 20% O 2 , respectively. In contrast, hyperoxia (40% O 2 ) significantly inhibited EPO production.…”
Section: Hyperoxia Therapy In Non-pulmonary Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that atmospheric and hyperbaric hyperoxia can reduce the hypoxic area of tumors to varying degrees. [300][301][302][303] The EPO levels in hepatoblastoma HepG2 cells treated with 5% O 2 and 1% O 2 were 2.5 and 4 times higher than those in cells treated with 20% O 2 , respectively. In contrast, hyperoxia (40% O 2 ) significantly inhibited EPO production.…”
Section: Hyperoxia Therapy In Non-pulmonary Cancermentioning
confidence: 99%
“…391,392 In a mouse model of bladder cancer treated with a combination of HBO and nimustine, there was a therapeutic effect on a subset of bladder tumors. 393 GBM is a highly malignant primary brain tumor originating from the glial tissue of the central nervous system, 394 and resistance to the chemotherapeutic drug temozolomide is commonly responsible for most 302 disease recurrences. [395][396][397] Experimental results showed that hyperoxia leads to dysregulation of protein folding, which in turn induces apoptosis mediated by the unfolded protein response.…”
Section: Application Of Hyperoxia In Chemotherapymentioning
confidence: 99%
“…The development of efficient oxygen delivery strategies is valuable and significant for enhancing the effect of tumor therapy. At present, hyperbaric oxygen is inhaled and used clinically during tumor treatment to force more oxygen into the blood and tumors ( Chu et al, 2018 ; Liu et al, 2021 ; Li et al, 2022b ). However, this strategy cannot overcome the defect of insufficient oxygen supply caused by vessel structural abnormity, and it is difficult to effectively transport oxygen to the interior of the tumor.…”
Section: Nanomaterial-mediated Tumor Hypoxia Reliefmentioning
confidence: 99%
“…Other reports showed that the hypoxic microenvironment within HCC inhibited the expression of cGAS. Therefore, cGAS-mediated DNA recognition and STING-TBK1-IRF3 pathway activation were inhibited [ 87 , 88 ]. Moreover, some tumors can evade the immune system by suppressing STING.…”
Section: Nash-associated Hcc and Stingmentioning
confidence: 99%